Improved organic coating delamination resistance using physical vapour deposited Zn-Mg layers on strip steel - REBECCA BOLTON (2021)
Physical vapour deposition (PVD) of zinc alloy coatings was investigated as a potential substitute process for commercially available hot dip galvanising (HDG) of strip steel. Therefore, zinc alloy coatings deposited by PVD were systematically compared with traditional sacrificial HDG zinc alloy coatings, in terms of bare metal corrosion resistance and resistance to corrosion-driven delamination of an organic overcoat, to establish the effects of magnesium content, microstructure and surface treatment. The effectiveness of modern corrosion inhibitor pigments, of known volume fraction, on HDG and PVD zinc coatings was also explored. All PVD coatings and commercially available HDG coatings were characterised using microscopy techniques and x-ray diffraction to identify the microstructure and phases present as a function of magnesium content. It was confirmed that the PVD coatings were significantly thinner than the HDG coatings. The pure zinc PVD coating was comprised of hexagonal microplates, whereas the HDG counterpart contained grains 5-10 time larger. The PVD coating containing 4 wt% magnesium exhibited a discrete structure, a binary system of zinc-rich and Mg2Zn11-rich phases, much finer than the HDG Zn-Mg-Al (ZMA) coating. The PVD coatings containing 10 wt% and 20 wt% magnesium were studied using transmission electron microscopy as they possessed nanostructures containing Mg2Zn11 and MgZn2 phases respectively. Open circuit potential (OCP) measurements in chloride-containing solution established that an increase in magnesium content in PVD coating resulted in a decrease in the initial immersion open circuit potential. Additionally, increased magnesium content in the PVD layers also correlated with an increase in corrosion resistance, as made evident by reduced Ecorr and Icorr values during potentiodynamic studies. Electrochemical impedance spectroscopy (EIS) comparative studies suggested an improvement in corrosion resistance exhibited by PVD0 compared to HDG, both zinc-only coatings, attributed to the finer and more compact surface morphology. Bare metal corrosion response for all coatings was studied using a novel augmentation of the scanning vibrating electrode technique (SVET), known as SVET-TLI (time-lapse imaging). The combination of electrochemical mapping and photographic imagery revealed a potential optimum magnesium content within the PVD coatings. PVD4 exhibited the lowest anodic current density over a 24 hour study compared to the HDG, ZMA and other PVD coatings. Furthermore, the characteristic black staining attributed to magnesium corrosion was observed on the magnesium-containing PVD coatings. However, on the PVD Zn-Mg coatings the staining was observed in the regions established as net cathodes, which is contrary to association of staining with magnesium dissolution which takes place in local anodes. Using the scanning vibrating kelvin probe (SKP) method, PVD4 was identified as the optimum magnesium composition as it was found to be resistant of both corrosion-driven cathodic delamination and anodic undermining. Cathodic delamination was observed on the zinc-only coatings, PVD0 and HDG, as well as PVD10 (although at a much slower rate). ZMA and PVD20, both MgZn2-containing systems, showed resistance to cathodic delamination and evidence of anodic undermining. Exploring several modern inhibitive pigments incorporated in the organic overcoat allowed the identification of a commercial pigment “PAM” to provide the greatest improvement in delamination resistance for the zinc-only metallic coatings.